2022
DOI: 10.18280/ijdne.170520
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of One-Dimensional Collapse for Highly Gypseous Soils

Abstract: The presence of gypsum in soils has a notable impact on their engineering properties. Since the gypsum dissolved due to water percolation, their properties may change over time. Collapsibility is considered the most significant parameter ruling the characteristics of highly gypseous soils for several decades; standards have tried to find the best formula for expressing the amount of strain in collapsing soils. Starting from the single and double odometer test, coming to the one-dimensional collapse. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They need an open metastable structure or open porous fabric to be developed using various bonding procedures. (Al-Mukhtar and Al-Obaidi, 2022) and (Fattah et al, 2015) and reported that when soils are initially dry, volume changes that lead to collapse frequently happen in non-plastic or extremely low plasticity soils and are quicker than those seen during consolidation processes. Furthermore, inadequate compaction techniques, low moisture levels, and waste items can also cause soil to artificially collapse.…”
Section: Introductionmentioning
confidence: 99%
“…They need an open metastable structure or open porous fabric to be developed using various bonding procedures. (Al-Mukhtar and Al-Obaidi, 2022) and (Fattah et al, 2015) and reported that when soils are initially dry, volume changes that lead to collapse frequently happen in non-plastic or extremely low plasticity soils and are quicker than those seen during consolidation processes. Furthermore, inadequate compaction techniques, low moisture levels, and waste items can also cause soil to artificially collapse.…”
Section: Introductionmentioning
confidence: 99%
“…When the gypseous soil is exposed to water, the collapsibility of the soil will be increased. The dissolution of salts inside the soil mass will create new pores inside the soil structure and lose the bonds between the soil particles, leading to the metastable structure [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%